Experiential Marketing in the Street Coffee Phenomenon of Yogyakarta - kusumantara, desta noer; Haq, Mochammad Fauzul (Jurnal Paradigma, 2026)
The current development of the coffee industry shows remarkable growth. Coffee businesses have experienced an increase driven by the rising trend of coffee drinking (“ngopi”) among young people. The emergence of the Street Coffee phenomenon is one of the cultural expressions of this trend, spreading across various social groups. In Yogyakarta, the Street Coffee phenomenon has grown due to a shift from the conventional practice of drinking coffee in indoor coffee shops to enjoying it in roadside settings. One notable Street Coffee establishment in Yogyakarta is Kedai 31 Bloc. This study aims to explore the experiential marketing strategies implemented by Kedai 31 Bloc. Using a qualitative descriptive method, data were collected through in-depth interviews with the café’s employees. The study employs the experiential marketing component model to analyze the strategies utilized by the café in its efforts to increase customer engagement and attract more consumers. Keyword: Coffee Businesses, Experiential Marketing, Street Coffee Phenomenon.